Computational modelling of the equine arteritis virus GP5/M Dimer: Implications for immune evasion and virulence - Michael Veit; Anna Karolina Matczuk (PLoS ONE, 2026)
Equine arteritis virus (EAV) is a positive-stranded RNA virus of the Arteriviridae family. Its GP5/M dimer, the principal component of the viral envelope, mediates virus budding and serves as a key target for neutralizing antibodies. Using AlphaFold3, we predicted the 3D structure of the EAV GP5/M dimer and compared it to its homolog in porcine reproductive and respiratory syndrome virus (PRRSV). Both complexes share a conserved architecture comprising a short ectodomain, three helical transmembrane regions, and a β-sheet-rich endodomain. EAV GP5 features a longer ectodomain with four α-helices and a disulfide-linked β-sheet, which forms the most variable and surface-exposed region containing neutralizing epitopes. Adjacent conserved and variable N-glycosylation sites suggest immune evasion mechanisms involving antigenic drift and glycan shielding. Another epitope, located in a membrane-proximal helix, overlaps with known virulence and persistence determinants. The transmembrane domains are the most structurally conserved regions between EAV and PRRSV, characterized by tilted and kinked helices stabilized by hydrophilic interactions within the lipid bilayer. These findings provide molecular insights into the structural organization, immune targets, and virulence-associated features of the GP5/M dimer, offering a foundation for rational vaccine design against EAV.